GE_GERICHTE P/16615/2020 vom 23. Dezember 2020 - GE Cour de justice (2020)
ORDONNANCE DE CLASSEMENT;IMPUTATION;TORT MORAL;ORDONNANCE PÉNALE;DÉTENTION PROVISOIRE;RADIATION DU RÔLE | CPP.319; CP.51; CPP.429.al1.letc